Fé e saber em Habermas: a reserva semântica da religião na sociedade secularizada - Schuck, Neivor (2010)
Habermas considers religion as an important issue in contemporary semantics. We are living in a post metaphysical period and the proposal of a universal autonomy of religion does not have any support anymore. At the initial moment we work in the evolution of Habermas' thought till reaching to consider a philosophy of religion. In the second moment, we explore the possibility of philosophy of religion in Habermas. This leads one to consider the possibility of a semantic reserve of religion in a secular society. Thus, the Habermas' perspective of thinking takes into account the knowledge that is originated from religion when he opens space in the public realm for this discussion, being a epistemology of faith. This openness would make possible the philosophy of religion to think in a opaque core around the religion experience